Correction: Nanoarchitectonics of p-type BiSbTe with improved figure of merit via introducing PbTe nanoparticles. Issue 61 (2nd December 2021) - Li, Yuanyue; Ren, Mengna; Sun, Zhongsen; Yao, Zhao
Abstract : Correction for 'Nanoarchitectonics of p-type BiSbTe with improved figure of merit via introducing PbTe nanoparticles' by Yuanyue Li et al., RSC Adv., 2021, 11, 36636–36643, DOI: ; 10.1039/D1RA07138F .